2018
DOI: 10.1159/000488505
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Meal Ingestion on Liver Stiffness and Controlled Attenuation Parameter

Abstract: Background and Aims: Despite the increasing use of noninvasive methods for the assessment of liver fibrosis and steatosis, the effect of fasting and food intake on these parameters is not yet clear. Our aims were to evaluate the effect of food intake on liver stiffness (LS) (measured by transient elastography) and controlled attenuation parameter (CAP) in patients with different degrees of liver disease and healthy volunteers, and secondarily, to assess possible factors associated with variations of LS and CAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
3
11
0
Order By: Relevance
“…In our study, we found a significant statistical difference in TE values in patients with chronic liver disease (p = 0.02). These data are in accordance with previous works [16][17][18]. In fact, in the study by Arena et al [17], with a fibrosis stage validated by histology, a higher LS value was found between 15 and 45 min after meal intake in all patients, with more pronounced differences in cirrhotic individuals.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In our study, we found a significant statistical difference in TE values in patients with chronic liver disease (p = 0.02). These data are in accordance with previous works [16][17][18]. In fact, in the study by Arena et al [17], with a fibrosis stage validated by histology, a higher LS value was found between 15 and 45 min after meal intake in all patients, with more pronounced differences in cirrhotic individuals.…”
Section: Discussionsupporting
confidence: 92%
“…Also, Dauzat M et al [29] analyzed the volume of blood flow in portal vein after the intake of a fluid meal and showed that the blood flow already increased at 15 min and reached a maximum 30 min after food intake. Berzigotti et al [18] measured LS, portal vein vascular flow, and hepatic artery vascular flow after meal intake in cirrhotic patients. Postprandial hyperemia was accompanied by a marked increase in LS and these differences directly correlated with hepatic artery vascular flow (but surprisingly were not associated with differences in portal vein vascular flow).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations